The Influence of Implementation Change Management Education on Worker Professionalism at PT. Pojur Sumenep - Iriani Ismail; Asadi Khas (Edumaspul: Jurnal Pendidikan, 2023)
The purpose of this study was to ascertain the impact of changes brought about by the new PT regulations on the professionalism of the employees of PT. Pojur Sumenep. Post-Covid-19 Pojur Sumenep. This study is quantitative and uses questionnaire distribution as a method of data collecting. On 30 employees of PT. Pojur Sumenep, the sample was established using non-probability sampling and a saturation sampling technique. Simple linear regression analysis utilizing the SPSS application is the data analysis method used. The ratio indicates that 82.8% of the worker professionalism variable can be accounted for by the change management variable. While additional variables/factors outside of this research account for the remaining 17.2%.